Breaking the stronghold of food eaudiobook How we conquered food addictions and discovered a new way of living. - Brown, PhD, Michael L. (Tantor Media, 2018)
Are you sick and tired of being overweight? Are you fighting a losing battle with your waistline and eating yourself into the grave? Have you had it with feeling drained, discouraged, and run down because of obesity but find yourself enslaved to unhealthy eating habits? Are you convinced that God has a better way, but you simply can't break through? In their first-ever jointly authored book, Michael and Nancy Brown share the inspiring, practical, and humorous story of their own journey from obesity to vibrant health. If you want to break free from the stronghold of food and discover a wonderful new way of life, this book will show you the way.